Perceived Benefits and Barriers to Physical Activity among LGBTQ+ College Students. Issue 4 (11th October 2022) - Frederick, Ginny M.; Bub, Kristen L.; Evans, Ellen M.
ABSTRACT: Introduction/Purpose: Members of the lesbian, gay, bisexual, transgender, and queer (LGBTQ+) community experience health disparities in part due to health behaviors, including physical activity (PA). This cross-sectional study explored perceived benefits and barriers to PA, an important health behavior for both physical and mental health, among LGBTQ+ college students using quantitative and qualitative methods. Methods: College students identifying as LGBTQ+ ( n = 47) were assessed for PA via accelerometry and completed the Exercise Benefits and Barriers Scale (EBBS). Six focus groups (4–8 participants each) provided qualitative descriptions of perceived benefits and barriers to PA. Results: PA guidelines (aerobic and resistance training) were met by 30% of participants. Qualitative descriptions aligned with EBBS subscales of general benefits and barriers to PA. General minority stress, perceived stigma, internalized homophobia, and discrimination and violence emerged as themes related to the experienced barriers. Furthermore, effects of PA on body shape, focus on aesthetics in the LGBTQ+ community, the importance of physically active LGBTQ+ role models, deviance from social or gender norms related to PA, and same-sex relationships and body image were additional concerns related to LGBTQ+ identity. Conclusions: Qualitative responses indicate that LGBTQ+ college students perceive general benefits and barriers to PA. Barriers to engaging in sufficient PA due to minority stress and concerns related to identity as LGBTQ+ were evident. These findings can be used to develop tailored health promotion programs on college campuses to address the barriers to PA faced by LGBTQ+ students. More research is needed in the college-aged LGBTQ+ community to build robust PA health promotion efforts to enhance inclusivity and reduce health disparities.